(untitled) (Scientific journal of the Fergana State University, 2023)
The article provides information about the types of grain crops, wheat and its types, chemical composition, useful aspects of harvested wheat. It was determined and compared in the chemical analysis which wheat has more useful aspects before harvesting and after harvesting.